БАЛАНДЛИККА САКРОВЧИ ҚИЗЛАРНИНГ ЖИСМОНИЙ ТАЙЁРГАРЛИК МЕЗОНЛАРИ - Тўхтабоев, Н.Т. (SCIENCE and SOCIETY, 2022)
This article is obtained and analyzed the results of control tests of the physical fitness of female high jumpers, aimed at improving the physical fitness of athletes, were